Identification of a Novel SBP1-Containing SCFSFB Complex in Wild Dwarf Almond (Prunus tenella) - Zeng, Bin; Wang, Jianyou; Hao, Qing; Yu, Zhenfan; Abudukayoumu, Ayimaiti; Tang, Yilian; Zhang, Xiangfei; Ma, Xinxin (Frontiers in Genetics, 2019)
The S-RNase-based gametophytic self-incompatibility (SI), in which pistil and pollen specificities are determined by S-RNase and the S locus F-box protein respectively, has been found in the Solanaceae, Plantaginaceae, and Rosaceae families, but some underlying molecular mechanism remained elusive and controversial. Previous studies have discovered SI in wild dwarf almond (Prunus tenella), and pistil S (S-RNase) and pollen S (SFB) determinant genes have been investigated. However, the SCF (SKP1–Cullin1–F-box-Rbx1) complex, which functions as an E3 ubiquitin ligase on non-self S-RNase, has not been investigated. In current study, the PetSSK1 (SLF-interacting-SKP1-like1), SBP1(S-RNase binding protein 1), CUL1, SFBs (S-haplotype-speciﬁc F-box) were identified in an accession (ZB1) of P. tenella. Through yeast two-hybrid assays, it indicated that there were interactions between PetSBP1 and PetCUL1 and between PetSBP1 and PetSFBs (SFB16 and SFB17), and subsequent pull-down assays confirmed these interactions, suggesting a novel SBP1-containing SCFSFB complex in wild dwarf almond. Moreover, expect for putative interaction between PetSSK1 and PetCUL1, it revealed that PetSSK1 could not interact with PetSFB16 and PetSFB17, suggesting that the canonical SSK1-containing SCFSFB complex could not be identified. It further first suggested a novel molecular mechanism of gametophytic SI in Prunus species.